Effect of Clip Characteristics on Thermal Performance of Dr.MOS Packages - Hao-Lin Yen; Fang-I Lai (IEEE Access)
This study explores the impact of copper clip design on the thermal performance of driver MOSFET (Dr.MOS) packages with the goal of optimizing heat dissipation efficiency in microelectronic components. The study examines four key variables: clip thickness, material, attachment material, and plating material. The experimental results show that increasing the clip thickness from 0.15mm to 0.2mm leads to a 2.1% reduction in thermal resistance (from 3.3667°C/W to 3.2958°C/W). Furthermore, using copper C1100, which has higher thermal conductivity (391 W/m-K), further reduces thermal resistance, improving overall heat dissipation. Additionally, employing high-conductivity adhesives like SAC305 improves the thermal interface between the clip and wafer, while coatings such as graphene enhance thermal stability and corrosion resistance. Under high-voltage conditions (12V and 19V), the package with thicker copper clips and better attachment materials exhibited a significant reduction in surface temperature, dropping from 93.3°C to 71.7°C at 12V. These findings offer valuable insights for enhancing the thermal management efficiency of Dr.MOS packages, ensuring better reliability and longevity in high-power applications.